CRISPR/dual-FRET molecular beacon for sensitive live-cell imaging of non-repetitive genomic loci - Mao, Shiqi (Nucleic Acids Res, 2019)
Clustered regularly interspaced short palindromic repeats (CRISPR)-based genomic imaging systems predominantly rely on fluorescent protein reporters, which lack the optical properties essential for sensitive dynamic imaging. Here, we modified the CRISPR single-guide RNA (sgRNA) to carry two distinct molecular beacons (MBs) that can undergo fluorescence resonance energy transfer (FRET) and demonstrated that the resulting system, CRISPR/dual-FRET MB, enables dynamic imaging of non-repetitive genomic loci with only three unique sgRNAs.